Glucose metabolism in the brain in LMNB1‐related autosomal dominant leukodystrophy - Finnsson, Johannes (Acta Neurol Scand, 2018)
OBJECTIVE: LMNB1‐related autosomal dominant leukodystrophy is caused by an overexpression of the protein lamin B1, usually due to a duplication of the LMNB1 gene. Symptoms start in 5(th) to 6(th) decade. This slowly progressive disease terminates with death. We studied brain glucose metabolism in this disease using (18)F‐fluorodeoxyglucose positron emission tomography (PET). METHODS: We examined 8 patients, aged 48‐64 years, in varying stages of clinical symptomatology. Two patients were investigated with quantitative PET on clinical indications after which six more patients were recruited. Absolute glucose metabolism was analyzed with the PVElab software in 6 patients and 18 healthy controls. A semiquantitative analysis using the CortexID software was performed in seven investigations, relating local metabolism levels to global glucose metabolism. RESULTS: The clinical quantitative PET revealed low global glucose metabolism, with the most marked reduction in the cerebellum. In the PVElab analysis, patients presented low mean glucose metabolism in the cerebellum, brainstem and global grey matter. In the semiquantitative analysis, 2 patients showed a decreased metabolism in the cerebellum and 4 patients a relatively higher metabolism in parts of the temporal lobes. Since none of the patients showed an increased metabolism in the quantitative analysis, we interpret these increases as “pseudo‐increases” related to a globally reduced metabolism. CONCLUSIONS: Global reduction of grey matter glucose metabolism in this white matter disease most likely depends on a combination of cortical afferent dysfunction and, in later stages, neuronal loss. The lowest metabolism in the cerebellum is consistent with histopathological findings and prominent cerebellar symptoms.